A New 3-D Memristive Time-delay Chaotic System with Multi-scroll and Hidden Attractors. Issue 1 (2018) - Mohanty, Nalini Prasad; Dey, Rajeeb; Roy, Binoy Krishna
Abstract: In the recent era, memristor and time-delay are potential candidates for the construction of complex dynamical systems with special features. This paper proposes a novel time-delay chaotic system in the presence of a memristive device. The proposed system generates multi-scroll chaotic attractors without any equilibrium point. Such nature of a system is not reported in the literature yet to the best of authors' knowledge. The existence of rich chaotic behaviour in the proposed system is investigated by different numerical tools which include bifurcation diagram, frequency spectrum, instantaneous phase plot and attractors plot.